2017
DOI: 10.1096/fj.201601042rr
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa infection liberates transmissible, cytotoxic prion amyloids

Abstract: Patients who recover from pneumonia subsequently have elevated rates of death after hospital discharge as a result of secondary organ damage, the causes of which are unknown. We used the bacterium , a common cause of hospital-acquired pneumonia, as a model for investigating this phenomenon. We show that infection of pulmonary endothelial cells by induces production and release of a cytotoxic amyloid molecule with prion characteristics, including resistance to various nucleases and proteases. This cytotoxin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(120 citation statements)
references
References 61 publications
(106 reference statements)
6
112
0
1
Order By: Relevance
“…We previously reported that infection elicits the endothelial production of cytotoxic amyloids (22,53), which can be detected in the BALF of pneumonia patients. Neutralizing these amyloids alleviates cerebral endothelial disruption and rescues synaptic plasticity (23).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that infection elicits the endothelial production of cytotoxic amyloids (22,53), which can be detected in the BALF of pneumonia patients. Neutralizing these amyloids alleviates cerebral endothelial disruption and rescues synaptic plasticity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic supernatant was prepared and collected using previously described methods (21,22). Briefly, a colony-forming unit (CFU) per milliliter ratio of 2 3 10 8 CFU/ml at optical density (OD) 540 for both P. aeruginosa strain PA103 and the negative control strain DPcrV was previously determined and used.…”
Section: Preparation Of the Cytotoxic Supernatantmentioning
confidence: 99%
See 3 more Smart Citations